Alterations in gut microbial function following liver transplant. Issue 6 (13th May 2018) - Bajaj, Jasmohan S.; Kakiyama, Genta; Cox, I. Jane; Nittono, Hiroshi; Takei, Hajime; White, Melanie; Fagan, Andrew; Gavis, Edith A.; Heuman, Douglas M.; Gilles, Ho Chong; Hylemon, Phillip; Taylor‐Robinson, Simon D.; et al.
Abstract : Liver transplantation (LT) improves daily function and ameliorates gut microbial composition. However, the effect of LT on microbial functionality, which can be related to overall patient benefit, is unclear and could affect the post‐LT course. The aims were to determine the effect of LT on gut microbial functionality focusing on endotoxemia, bile acid (BA), ammonia metabolism, and lipidomics. We enrolled outpatient patients with cirrhosis on the LT list and followed them until 6 months after LT. Microbiota composition (Shannon diversity and individual taxa) and function analysis (serum endotoxin, urinary metabolomics and serum lipidomics, and stool BA profile) and cognitive tests were performed at both visits. We enrolled 40 patients (age, 56 ± 7 years; mean Model for End‐Stage Liver Disease score, 22.6). They received LT 6 ± 3 months after enrollment and were re‐evaluated 7 ± 3 months after LT with a stable course. A significant improvement in cognition with increase in microbial diversity, increase in autochthonous and decrease in potentially pathogenic taxa, and reduced endotoxemia were seen after LT compared with baseline. Stool BAs increased significantly after LT, and there was evidence of greater bacterial action (higher secondary, oxo and iso‐BAs) after LT although the levels of conjugated BAs remained similar. There was a reduced serum ammonia and corresponding rise in urinary phenylacetylglutamine after LT. There was an increase in urinary trimethylamine‐N‐oxide, which was correlated with specific changes in serum lipids related to cell membrane products. The ultimate post‐LT lipidomic profile appeared beneficial compared with the profile before LT. In conclusion, LT improves gut microbiota diversity and dysbiosis, which is accompanied by favorable changes in gut microbial functionality corresponding to BAs, ammonia, endotoxemia, lipidomic, and metabolomic profiles. Liver Transplantation 24 752–761 2018 AASLD.